The Effect of Screen Size on Students’ Cognitive Load in Mobile Learning - Talal Alasmari (STKIP Singkawang, 2020)
Mobile learning is becoming a crucial tool in this era of face-to-face shutdown of education, and however the whole process currently faces a significant deficiency due to the kind of cognitive load that does exist and its relation with mobile device screen display size. It is well-established that certain screen sizes are more effective than others. This study aims to investigate the effect of screen size on students’ cognitive load in mobile learning. Specifically, it investigates whether screen size has a role in cognitive role and draws a comparison to reflect on the most effective size to be used in the context of mobile learning. Other factors that might interfere in the process were also investigated which include course content, gender, age, and students' GPA to see whether they play any additional role in burdening the cognitive load when using different screen sizes. To test the effect of screen size on cognitive load, an online survey was distributed to 1,570 students of the University of Jeddah who are studying at the foundation year for the academic year of 2018-2018, particularly for eight online courses. The sample was chosen randomly, where all members of the population, 6,500 students, had equal opportunities to participate in the study. Participants were invited via e-mail by sending an invitation to participate along with the questionnaire link on the